2000
DOI: 10.1093/cercor/10.8.753
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and Complementary Projections of the Caudal Paralaminar Thalamic Nuclei to Rat Temporal and Insular Cortex

Abstract: Thalamic nuclei adjacent to the medial geniculate body play a pivotal role in processing of sensory stimuli during emotional situations. These nuclei, which include the suprageniculate nucleus (SG), the posterior intralaminar nucleus (PIN), the peripeduncular nucleus (PP) and the medial division of the medial geniculate body (MGm), project to both cortex and amygdala, but target areas and the extent of the projection of individual nuclei are not known yet. The aim of the present study was to analyze the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 72 publications
2
55
0
Order By: Relevance
“…The projection of neurons in the thalamic nuclei medial to the medial geniculate body to the insular and temporal cortices has also been described (Linke and Schwegler, 2000). The CGRP projections discussed above should represent at least a part of these projections.…”
Section: Cgrp Projections In the Forebrainmentioning
confidence: 96%
See 1 more Smart Citation
“…The projection of neurons in the thalamic nuclei medial to the medial geniculate body to the insular and temporal cortices has also been described (Linke and Schwegler, 2000). The CGRP projections discussed above should represent at least a part of these projections.…”
Section: Cgrp Projections In the Forebrainmentioning
confidence: 96%
“…2); thus we suggest that the CGRP cells in the suprageniculate nucleus should be included in the "CGRP nucleus" of the thalamus. The lateral part of the "CGRP nucleus" of the thalamus (the posterior intralaminar thalamic nucleus, the peripeduncular nucleus, and the suprageniculate thalamic nucleus), which was destroyed by our lesions medial to the medial geniculate body, and the medial division of the medial geniculate body have also been called the caudal paralaminar thalamic nuclei due to their location adjacent to the internal medullary lamina and their pattern of projection to the cerebral cortex (Linke and Schwegler, 2000).…”
Section: Cgrp Cell Bodiesmentioning
confidence: 99%
“…The projection patterns described are thus arranged into two large thalamocortical circuits: 1) topographic projection of thalamic core cells > middle cortical layers > superficial layers > deep layers, with reciprocal topographic feedback from layer VI back to both the core cells and to the overlying portion of nucleus reticularis; 2) matrix cells projecting nontopographically to layer I and receiving projections back from layer V, without interposed nucleus reticularis projections. Evidence suggests that the repeating thalamocortical, cortico-cortical, and corticothalamic projection patterns hold not only for primary sensory areas including VPM/VPL, LGd, and MGv to layer IV, and Pom, LP/Pul, and MGm to layer I of somatosensory, visual and auditory cortices, respectively (Killackey and Ebner, 1972;Ryugo and Killackey, 1974;Ribak and Peters, 1975;Herkenham, 1980;Kelly and Wong, 1981;Swadlow, 1983;Rieck and Carey, 1985;Herkenham, 1986;Jensen and Killackey, 1987;Winer and Larue, 1987;Scheel, 1988;Conley and Diamond, 1990;Rouiller and Welker, 1991;Bourassa and Deschenes, 1995;Huang and Winer, 2000), but also for a wide array of thalamic nuclei, intralaminar and nonintralaminar alike (Jones and Hendry, 1989;Rausell et al, 1992;Molinari et al, 1994;Molinari et al, 1995;Kuroda et al, 1998;Mitchell and Cauller, 2001;Rauschecker et al, 1997;Jones, 1998;Reep and Corwin, 1999;Linke and Schwegler, 2000;Jones, 2001)). For those cortical areas not receiving topographic projections from thalamus, the extensive topography-preserving cortico-cortical projections from superficial layers to recipient middle layers with reciprocal projections from the target's deep layers back to the source's superficial layers, may subserve a related function …”
Section: Anatomical Architecture Of Thalamocortical Circuitsmentioning
confidence: 99%
“…Layers 2/3 of primary ACx receives inputs from and project to other cortical regions (Wallace et al 1991;Winer 1992), whereas layers 3/4 receive thalamic input from the primary auditory relay in MGv (Mitani and Shimokouchi 1985;Winer 1992;Romanski and LeDoux 1993). The deeper layers 5/6 receive inputs from some nonprimary thalamic nuclei, including MGm, and project to cortical and subcortical targets (Jacobson and Trojanowski 1975;Caviness and Frost 1980;Kelly and Wong 1981;Linke and Schwegler 2000). Physiological studies have demonstrated signi®cant NMDAR-mediated EPSPs in layers 2±4 of ACx in young and juvenile rats (P3±P30; Ashe 1994, 1995;Aramakis and Metherate 1998).…”
Section: General Features and Implications Of Nr2a And Nr2b Mrna Distmentioning
confidence: 99%